2016
DOI: 10.1192/bjp.bp.115.170167
|View full text |Cite
|
Sign up to set email alerts
|

Thinking that one's life was in danger: perceived life threat in individuals directly or indirectly exposed to terror

Abstract: Perceived life threat may play a central role in the development and maintenance of PTSD in people directly as well as indirectly exposed to terror. Moderating perceptions of having been in serious danger may be an appropriate approach to the prevention and treatment of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
2
48
1
1
Order By: Relevance
“…This finding is in line with previous research indicating that perception of threat, rather than real risk, is the most important predictor of self-reported health problems and that people perceiving high threat are therefore a vulnerable group for reporting and possibly even for developing certain health problems (Blackburn & Epel, 2012; Heir et al, 2016; Nissen et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is in line with previous research indicating that perception of threat, rather than real risk, is the most important predictor of self-reported health problems and that people perceiving high threat are therefore a vulnerable group for reporting and possibly even for developing certain health problems (Blackburn & Epel, 2012; Heir et al, 2016; Nissen et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…It can be therefore hypothesized that the months preceding the attacks, during which Belgium was in a state of highest alert after the attacks in Paris in November 2015, could already have primed a negative impact on the population. Other studies also found that by anticipating disasters, peoples’ fears can worsen existing symptoms (Schuster et al, 2001) and that an on-going perceived threat may engender health problems (Heir et al, 2016; Nissen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the possibility that individuals can develop PTSD without directly experiencing the traumatic event, the criteria do not indicate whether indirect exposure can be through the media (e.g., watching the event unfold on television) or repetitive exposure to potential threats and harm via lockdown drills and related simulations. Researchers have emphasized the importance of the perceived threat of harm, which typically increases in relation to the proximity of the traumatic event (Heir et al, ). Silver, Holman, McIntosh, Poulin, and Gil‐Rivas () found similar results when studying a national probability sample of adults following the September 11th terrorist attacks against the World Trade Center.…”
Section: Introductionmentioning
confidence: 99%